Parancangan Sistem HACCP dan OPRP di PT. X - Glory Anastasia Leuw; Kriswanto Widiawan (Jurnal Titra, 2017)
The design of HACCP (Hazard Analysis Critical Control Point) and OPRP (Operational Pre Requisite Program) systems conducted at PT. X is implemented to maintain and increase customers’ trust. The design of these systems for chicken feed in the area of feed mill is the process of raw materials acceptance, raw material storage, production, and product storage. The design of HACCP and OPRP systems used seven principles of HACCP. There is a danger in OPRP such as Aflatoxin contamination at finished product in the packing area. However, there is no such danger in CCP (Critical Control Point). The design is verified by confirm design to the departments that contribute in the area of feed mill. The verification result revels that it is a good design and documented in the SOP (Standard Operating Procedure) of Quality Control Departement at PT. X.